Analysis Of The Influence Of Compensation, Work Discipline And Work Environment On Performance Of National Agribusiness Company Employees - Revi Sesario; Fatimah Malini Lubis; Ali Zaenal Abidin; Musran Munizu; La Ode Marihi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study aims to investigate the effects of work environment, motivation, remuneration, and work discipline on employee performance. Data for this study were gathered through the use of questionnaires, literature reviews, interviews, and observation. The population determination method employed in this study includes all employees. This study used a saturated sample technique to collect a total of 100 samples. The data from this investigation were examined with a multiple linear regression model. With respect to the results of the data analysis, the following deductions can be made: Discipline has a good and substantial impact on employee performance. Compensation has a beneficial, albeit small, impact on employee performance. Motivation has a good and significant impact on employee performance. The work environment has a positive and significant impact on employee performance. The independent factors work environment, motivation, compensation, and work discipline have a simultaneous positive and significant impact on the dependent variable employee performance.